Investigation of Micro Electrochemical Discharge Machining Tool with High Efficiency - Wang, Mingyu; Zhang, Jianhua; Liu, Yong; Li, Minghong (Recent Patents on Engineering, 2016)
Background: The fabrication of non-conductive hard and brittle materials like glass or some ceramics is always difficult. The electrochemical discharge machining (ECDM) process is a good selection for the fabrication of non-conductive hard and brittle materials. Objective: In order to achieve the high efficiency machining of non-conductive hard and brittle materials, a micro electrochemical discharge machining tool is established in this paper and various relevant patents have been discussed. Method: Firstly, the control and force feedback system is constructed. Secondly, the enhancement of the electrolyte refreshment and the mass transfer in the narrow machining gap using the rotating tool electrode is investigated. Finally, many experiments are carried out including ECDM drilling and milling. Results: Arrary of micro holes with about 168μm entrance, 155μm exit and 6% taper ratio and a micro groove are fabricated successfully on Pyrex glass. The feed rate of the drilling process is about 2μm/s and the milling process is 4μm/s. It shows that the machine tool system can meet the requirements of micro electrochemical discharge machining process and improve the machining efficiency greatly.
Keywords: pyrex glass